Crystal structure of bis(benzyltriethylammonium) hexachlorotellurate(IV), [C7H7(C2H5)(3)N](2)(TeCI6) - Caracelli, I (R Oldenbourg Verlag, 2004)
C26H44Cl6N2Te, monoclinic, P12(1)/n1 (no. 14), a = 9.3981(5) Angstrom, b = 14.606(1) Angstrom, c = 12.4524(7) Angstrom, beta = 108.335(5)degrees, V = 1622.6 Angstrom(3), Z = 2, R-gt(F) = 0.024, wR(ref)(F-2) = 0.065, T = 293 K.